2015
DOI: 10.7860/jcdr/2015/12261.5742
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin E, Interleukin-18 and Interleukin-12 in Patients with Atopic Dermatitis: Correlation with Disease Activity

Abstract: These findings support an association between IgE, IL-18 or IL-12/p40 and AD. The stronger response observed in serum samples from patients with higher SCORAD scores suggest that IgE, IL-18 and IL-12/p40 may be useful in evaluating the progression of AD and in elucidating the mechanisms of disease pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 30 publications
3
35
0
Order By: Relevance
“…Elevated expression of serum IL‐18 is seen in children and murine models . It has been shown to be elevated in the SC of adults with AD and in the serum of infants and children with AD, correlating with disease activity . We also found CXCL8 (IL‐8) to be significantly increased in the SC and correlated with disease severity and barrier dysfunction, further supporting the role of innate activation.…”
Section: Discussionsupporting
confidence: 64%
“…Elevated expression of serum IL‐18 is seen in children and murine models . It has been shown to be elevated in the SC of adults with AD and in the serum of infants and children with AD, correlating with disease activity . We also found CXCL8 (IL‐8) to be significantly increased in the SC and correlated with disease severity and barrier dysfunction, further supporting the role of innate activation.…”
Section: Discussionsupporting
confidence: 64%
“…The IgE sensitization and severity of many atopic disorders were well studied and connected with each other particularly for AD progression and BA persistence (23,24). Previously we also concluded that IgE is useful in evaluating the progression of AD and in elucidating the mechanisms of disease pathogenesis (6). In this study, we found that the serum levels of total IgE in patients with different atopic disorders were significantly higher as compared with healthy controls.…”
Section: Discussionsupporting
confidence: 51%
“…To prove this hypothesis, we determined the serum levels of filaggrin protein in patients with BA, AR, AD and also in those atopic patients, which were affected by multiple atopic disorders (mixed atopic patients). Not only have we measured these, we also determined the levels of IgE as a positive control for the allergic patients as studies have shown a well-defined association between serum IgE levels with allergic disorders (5,6). Bronchial hyperactivity has long been recognized as a hallmark of a number of allergic disorders but it's association with the dysfunctioning of mast cells and eosinophils is still not completely defined and remains controversial (7,8).…”
mentioning
confidence: 99%
“…Monocyte-derived dendritic cells induced by Malassezia furfur in peripheral blood stimulate the production of IL-18 in addition to that of TNF-α and IL-1β [ 54 ]. Additionally, Zedan et al [ 55 ], reported that AD severity (SCORAD score) correlates with the serum IL-18 concentration. Furthermore, chronic stress suppresses the HPA axis and aggravates Th2 immune responses with the lack of immunosuppressive effects in allergic diseases [ 56 ].…”
Section: Il-18 In Inflammatory and Autoimmune Cutaneous Diseasesmentioning
confidence: 99%